The Economic Impacts of the Qosh Tepa Canal on the Agricultural Sector - Husain khail, Miraqa; Ahmadzai, Khalmohamad (Journal of Natural Sciences – Kabul University, 2024)
Afghanistan is recognized as an agricultural country, with approximately 80% of its population reliant on agriculture for their livelihoods. However, decades of conflict and a growing population have significantly hindered Afghanistan's agricultural productivity, leaving the country heavily dependent on imports for nearly all agricultural products. Water is one of Afghanistan's most vital natural resources and plays a crucial role in the development of agriculture and livestock. Afghanistan possesses an annual water resource of 75 billion cubic meters. Yet, a large portion of this water—approximately 37 billion cubic meters—flows freely to neighboring countries without being utilized, while only 20 billion cubic meters are used domestically. Unfortunately, Afghanistan is not self-sufficient in food production, necessitating the development of strategies to produce food locally. The country has abundant natural resources, including land, water, and favorable climatic conditions, which, if effectively managed, could pave the way toward food self-sufficiency. The primary objective of this study is to examine the Qosh Tepa Canal, its characteristics, and its economic benefits. Data for the study were gathered from technical reports and scholarly articles using a library-based research method.